2013
DOI: 10.1116/1.4792515
|View full text |Cite
|
Sign up to set email alerts
|

Causes and elimination of pyramidal defects in GaSb-based epitaxial layers

Abstract: Electrical properties and deep traps spectra of N-polar and Ga-polar AlGaN films grown by molecular beam epitaxy in a wide composition range

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Precise control of substrate temperature is of principal importance for the ternary AlSb y As 1−y (Sample D) and the quaternary Al x Ga 1−x Sb y As 1−y (Sample E) layers since it directly controls the incorporation ratio of Sb and As and thus the lattice parameter. Growth of Al(Ga)SbAs compounds (Samples D and E) following the hydrogen-assisted oxide removal process enables smooth buffer layers to be grown free of pyramidal defects typically observed on the sur-face of GaSb grown on GaSb [17].…”
Section: Molecular Beam Epitaxy Growth and Device Fabricationmentioning
confidence: 99%
“…Precise control of substrate temperature is of principal importance for the ternary AlSb y As 1−y (Sample D) and the quaternary Al x Ga 1−x Sb y As 1−y (Sample E) layers since it directly controls the incorporation ratio of Sb and As and thus the lattice parameter. Growth of Al(Ga)SbAs compounds (Samples D and E) following the hydrogen-assisted oxide removal process enables smooth buffer layers to be grown free of pyramidal defects typically observed on the sur-face of GaSb grown on GaSb [17].…”
Section: Molecular Beam Epitaxy Growth and Device Fabricationmentioning
confidence: 99%
“…In such devices, the performance of every single pixel is crucial for the operation of the entire device. The complex studies on defects reduction in InAs/GaSb superlattices are still carried out by many research groups around the world [ 20 , 21 ]. For example, Walther et al [ 22 ] reported that using a good quality substrate, optimization of the growth, and post-growth processing can result in defects-free single pixels.…”
Section: Introductionmentioning
confidence: 99%
“…They are typically buried with a thick buffer layer and below a diffusion barrier. 24 It is likely such contamination also occurs in the base layers of the NW. In the NW interior, irregularities such as short segment wurtzite/zincblende stacking faults, twin boundaries, and polytypism are commonly observed.…”
mentioning
confidence: 99%